Up in the air: Evidence of dehydration risk and hong-haul flight on athletic performance - Zubac, D.; Buoite Stella, A.; Morrison, S. A. (Nutrients, 2020)
The microclimate of an airline cabin consists of dry, recirculated, and cool air, which is maintained at lower pressure than that found at sea level. Being exposed to this distinctive, encapsulated environment for prolonged durations, together with the short-term chair-rest immobilization that occurs during long-haul flights, can trigger distinct and detrimental reactions to the human body. There is evidence that long-haul flights promote fluid shifts to the lower extremity and induce changes in blood viscosity which may accelerate dehydration, possibly compromising an athlete`s potential for success upon arrival at their destination. Surprisingly, and despite several recent systematic reviews investigating the effects of jet lag and transmeridian travel on human physiology, there has been no systematic effort to address to what extent hypohydration is a (health, performance) risk to travelers embarking on long journeys. This narrative review summarizes the rationale and evidence for why the combination of fluid balance and long-haul flight remains a critically overlooked issue for traveling persons, be it for health, leisure, business, or in a sporting context. Upon review, there are few studies which have been conducted on actual traveling athletes, and those that have provide no real evidence of how the incidence rate, magnitude, or duration of acute dehydration may affect the general health or performance of elite athletes.